NAUTILOIDS WITH PROCHOANITIC SEPTAL NECKS - Zhuravleva F.A. (My University, 2002)
A new oncocerid genus, Thonoceras (type species T. lichutinense sp. nov.), with prochoanitic septal necks is described from the Upper Devonian of Novaya Zemlya.